Ultrasound Transmission Tomography Imaging of Structure of Breast Elastography Phantom Compared to US, CT and MRI - Krzysztof OPIELIŃSKI; Piotr PRUCHNICKI; Tadeusz GUDRA; Przemysław PODGÓRSKI; Tomasz KRAŚNICKI; Jacek KURCZ; Marek SĄSIADEK (Archives of Acoustics)
The paper presents an analysis of the results of ultrasound transmission tomography (UTT) imaging of the internal structure of a breast elastography phantom used for biopsy training, and compares them with the results of CT, MRI and, conventional US imaging; the results of the phantom examination were the basis for the analysis of UTT method resolution. The obtained UTT, CT and MRI images of the CIRS Model 059 breast phantom structure show comparable (in the context of size and location) heterogeneities inside it. The UTT image of distribution of the ultrasound velocity clearly demonstrates continuous changes of density. The UTT image of derivative of attenuation coefficient in relation to frequency is better for visualising sharp edges, and the UTT image of the distribution of attenuation coefficient visualises continuous and stepped changes in an indirect way. The inclusions visualized by CT have sharply delineated edges but are hardly distinguishable from the phantom gel background even with increased image contrast. MRI images of the studied phantom relatively clearly show inclusions in the structure. Ultrasonography images do not show any diversification of the structure of the phantom. The obtained examination results indicate that, if the scanning process is accelerated, ultrasound transmission tomography method can be successfully used to detect and diagnose early breast malignant lesions. Ultrasonic transmission tomography imaging can be applied in medicine for diagnostic examination of women’s breasts and similarly for X-ray computed tomography, while eliminating the need to expose patients to the harmful ionising radiation.